Effect of Medication and Freezing of Gait on Rambling and Trembling in Quiet Standing in Individuals With Parkinson’s Disease - Cupertino, Layla (2025)
Background: Individuals with Parkinson’s disease (PD) with freezing of gait (FoG) exhibit difficulty with changes in sensory input, indicating a potential sensorimotor integration deficit. Understanding how levodopa impacts balance particularly in FoG, is critical. As traditional postural sway measures may not fully capture the complexity of balance control, rambling and trembling decomposition of the center of pressure allows a more detailed assessment of postural control by distinguishing between supraspinal and spinal contributions, offering insights into sensorimotor integration deficits. This study aims to analyze the effects of medication and FoG on rambling and trembling in quiet standing in individuals with PD. Methods: We analyzed 13 individuals with PD with FoG (PD freezers) and 19 individuals with PD without FoG (PD nonfreezers) while quiet standing on a rigid and malleable surface under (ON) and without (OFF) dopaminergic medication. Area, root mean square, and mean velocity were calculated for rambling and trembling trajectory. Results: For the rambling, all variables were significantly higher on the malleable compared with the rigid surface. For trembling, (a) all variables were higher on the malleable compared with the rigid surface (p < .001), and (b) area and medial–lateral root mean square were significantly higher ON compared with OFF medication for both groups of participants similarly. Conclusion: Our results strengthen the evidence that PD freezers have the same postural sway in quiet posture as PD nonfreezers, using similar mechanisms to control the posture. In addition, levodopa influences spinal mechanisms more than supraspinal ones in individuals with PD in quiet standing.